﻿High altitude morphotype of the widespread Lobrathium multipunctum (Gravenhorst, 1802) (Coleoptera, Staphylinidae, Paederinae) revealed by DNA-barcoding - Aslak Kappel Hansen; Josh Jenkins Shaw (Contributions to Entomology)
High altitude ecosystems are often home to endemic species that have evolved in isolation from their low elevation counterparts. In many cases, especially in insects, such mountain endemics are often apterous (due to their reduced ability to fly and disperse). In most cases, so far, these mountain endemics are genetically differentiated from lowland sister species or populations. During an excursion in Central Spain, we encountered two such strikingly different morphotypes of the rove beetle Lobrathium multipunctum (Gravenhorst, 1802) (Coleoptera, Staphylinidae, Paederinae). The morphotype from high elevation was smaller and paler than those at low elevation, which were slightly larger, darker and regularly coloured. The high altitude morphotype was earlier considered a separate species (Lobrathium hispanicum Dodero, 1916) from its widespread lower-land counterpart (Lobrathium multipunctum (Gravenhorst, 1802)) before their relatively recent synonymy. Using the cytochrome c oxidase subunit I (COI) barcode region, we tested whether these distinct morphotypes are distinct species. We found that their synonymy is supported, based on multiple species delimitation methods. We suggest that this phenomenon may be more widespread amongst insects and other organismal groups. We note that the presence of high altitude morphotypes which are phylogenetically nested within, or genetically identical to, widespread lowland species (regular morphotype) is rarely reported in the literature on beetles (and other insects). These findings thus highlight the need for caution when describing mountain endemics and further highlight DNA barcoding as a helpful tool for their study.